2003
DOI: 10.1902/jop.2003.74.6.815
|View full text |Cite
|
Sign up to set email alerts
|

Crown Lengthening in Mandibular Molars:A 5‐Year Retrospective Radiographic Analysis

Abstract: A critical distance from the furcation (CDF) of 4 mm was established as a landmark under which, if surgery was performed on mandibular molars, chances of furcation involvement in the future were very high.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 14 publications
0
25
0
3
Order By: Relevance
“…These observations may corroborate prior studies about the healing of transplanted teeth using non-rigid fixation technique. 9,10,12,16 CONCLUSION: The clinical findings presented here suggest that this protocol offers several advantages over the conventional surgical approaches and can be used successfully to treat severely damaged tooth without functional and esthetic deformities, especially in the anterior region where esthetic is of great concern. …”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…These observations may corroborate prior studies about the healing of transplanted teeth using non-rigid fixation technique. 9,10,12,16 CONCLUSION: The clinical findings presented here suggest that this protocol offers several advantages over the conventional surgical approaches and can be used successfully to treat severely damaged tooth without functional and esthetic deformities, especially in the anterior region where esthetic is of great concern. …”
Section: Discussionmentioning
confidence: 80%
“…Clinical crown lengthening in esthetic areas requires a more reliable and sophisticated diagnostic process and treatment modality selection. 12 The surgical extrusion technique for clinical crown lengthening described here was successful from both esthetic and functional point of view since resective osseous surgery was not done. Several studies had demonstrated the clinical feasibility of surgical extrusion with favorable short and longterm results, and suggest that this method is much more economical than implant or fixed partial denture treatment.…”
Section: Discussionmentioning
confidence: 91%
“…A faixa etária dos 23 pacientes selecionados, com ausência de alteração no nível de inserção clínica nos sítios M e D dos dentes pré-molares, foi de 20 a 45 anos de idade, menor do que aquela relatada em outros estudos 12,19,35,49 . A causa mais freqüente para indicação cirúrgica foi a presença da cárie dentária, seguido da fratura dentária, numa distância ≤2mm O controle profissional das áreas tratadas cirurgicamente foi realizado semanalmente para assegurar efetivo controle de placa no primeiro mês pós-cirúrgico, e mensalmente, até completar 6 meses de avaliação.…”
Section: A B C D E F G Hunclassified
“…Esse mesmo cuidado foi tomado por HERRERO et al 28 (1995) para excluir a influência de fatores relacionados aos procedimentos restauradores na reparação dos tecidos periodontais marginais. Diferente da maioria dos estudos encontrados na literatura 12,18,19,35 , onde tratamentos restauradores definitivos foram iniciados antes da finalização do estudo.…”
Section: ) Quantidade De Ressecção óSseaunclassified
See 1 more Smart Citation